Heteropterys tomentosa A. Juss: Toxicological and adaptogenic effects in experimental models. Issue 4 (December 2017) - Fraga, Géssica Alves; Balogun, Sikiru Olaitan; Pascqua, Emilly Della; de Oliveira, Ruberlei Godinho; Botelho, Guilherme; Pavan, Eduarda; da Rosa Lima, Thiago; Avila, Eudes Thiago Pereira; de Medeiros Amorim Krueger, Clarissa; Filho, Valdir Cechinel; Damazo, Amílcar Sabino; de Oliveira Martins, Domingos Tabajara; et al.
Background: The constant pursuit of improved athletic performance characterizes high-performance sport and the use of medicinal plants as dietary supplements is becoming widespread among athletes to enhance long-term endurance performance. Aim: The present study evaluated the toxicity of Heteropterys tomentosa (HEHt) and its acute adaptogenic effects. Methods: The in vitro safety profile was evaluated on CHO-k1 cells using the alamar Blue assay, at concentrations ranging from 3.125 to 200 µg/mL. In vivo acute oral toxicity was conducted in male and female mice with oral administration of graded doses of HEHt from 400 to 2000 mg/kg. A subchronic oral toxicity study was completed by oral administration of HEHt (50, 200 or 1000 mg/kg) and vehicle for 30 days in male Wistar rats. Clinical observations and toxicological related parameters were determined. Blood was collected for biochemical and hematological analyses, while histological examinations were performed on selected organs. Thereafter, an adaptogenic test consisting of progressive loads until exhaustion was conducted in rats ( n = 5/group) orally pre-treated with the vehicle and HEHt (25, 100 or 400 mg/kg). Results: HEHt exhibited no cytotoxic effects on the CHO-k1 cells and, apparently, no acute toxicity in mice and no subchronic toxicity in rats. An ergogenic effect was observed only at the dose of 25 mg/kg compared with the vehicle in relation to time to exhaustion and exercise load ( p = .011 and .019, respectively). HEHt is safe at up to 400 mg/kg, contains astilbin and taxifolin as the major phytochemical compounds, and exhibited a potential adaptogenic effect. Conclusions: These results justify its anecdotal usage as a tonic, show that the hydroethanolic maceration of the root does not cause toxicity, and provide scientific evidence of its potential as a source of new adaptogenic substance(s).